PUBLIC-PRIVATE INNOVATION MANAGEMENT: FINANCIAL CONTENT IN THE EPISTEMIC TERMS OF INTERNATIONAL TRANSACTIONAL POLICY (World of finance, 2025)
Вступ. Масштабування інноваційної екосистеми потребує цифрової трансформації публічно-приватного управління інноваціями (ППУІ). Трансакційна політика, яка гарантує обмін ресурсами, формує міжнародні контури розвитку глобалізованої економіки з локальними преференціями. ППУІ стикається з геополітичними, регуляторними та комунікаційними викликами, що вимагають міжнародної співпраці для забезпечення цифрової трансформації в умовах епістемічності. Актуалізується науковий дискурс щодо децентралізованих фінансів (DeFi) та криптовалюти, які прагнуть відтворити основні економічні функції традиційних фінансів (TradFi), але їхні унікальні характеристики породжують нові ризики для фінансової стабільності.Мета – обґрунтувати теоретичний концепт масштабування інновацій із фокусуванням на трендах публічно-приватного управління інноваційною трансформацією в умовах епістемічності міжнародної трансакційної політики.Результати. Цифрова трансформація сприяє синергії держави та бізнесу, особливо в Україні, де ППУІ активізує інновації в модернізації оборонного сектору. Трансакційна політика забезпечує захист інтелектуальної власності та гармонізацію стандартів через програми інноваційного розвитку Horizon Europe, які доцільно адаптувати і масштабувати для досягнення національних безпекових гарантій. Аргументовано, що блокчейн і DeFi трансформують фінансовий контент, але створюють регуляторні виклики. Гравітаційна модель розкриває спекулятивну роль нативних криптоактивів і транзакційну – стейблкойнів, актуалізуючи адаптивність регулювання для зниження ризиків і підтримки інноваційних технологій. Застосування новітніх регуляторних заходів, зокрема вбудовування правил у смарт-контракти, відповідатиме принципам технологічно нейтрального регулювання, що дає змогу балансувати між інноваціями та стабільністю.Перспективи. Подальший розвиток ППУІ потребує дослідження комунікації DeFi з традиційними фінансами, зокрема токенізації активів і смарт-контрактів, для мінімізації системних ризиків. Важливим є діагностування стабільності стейблкойнів та їхнього впливу на фінансову інклюзію в країнах, що розвиваються. Регулювання децентралізованих систем, як DAO, сприятиме фінансовій стабільності та визначенню меж взаємодії із регуляторами. Впровадження ШІ потребує етичних стандартів для забезпечення прозорості та безпеки. В Україні кластер Brave1 демонструє потенціал ППП для інновацій в умовах невизначеності, а модернізація КСВ з урахуванням трендів трансакційної політики гармонізуватиме економічні й оборонні цілі, сприяючи сталому розвитку та адаптації глобальних стандартів до локальних вимірів. Introduction. Scaling the innovation ecosystem requires a digital transformation of publicprivate innovation management (PPIM). Transactional policies that guarantee the exchange of resources shape the international contours of the development of a globalized economy with local preferences. PPIM faces geopolitical, regulatory and communication challenges that require international cooperation to ensure digital transformation in the face of epistemic uncertainty. There is a growing academic discourse on decentralized finance (DeFi) and cryptocurrencies, which seek to replicate the core economic functions of traditional finance (TradFi), but their unique characteristics create new risks to financial stability.The purpose of the article is to substantiate the theoretical concept of scaling innovations with a focus on trends in public-private management of innovation transformation in the context of the epistemic nature of international transactional politics.Results. Digital transformation promotes synergy between the state and business, especially in Ukraine, where the PPIM activates innovation in the modernization of the defense sector. Transactional policy ensures the protection of intellectual property and the harmonization of standards through Horizon Europe innovation development programs, which can be adapted and scaled to achieve national security guarantees. It is argued that blockchain and DeFi are transforming financial content, but they also create regulatory challenges. The gravity model reveals the speculative role of native cryptoassets and the transactional role of stablecoins, highlighting the adaptability of regulation to reduce risks and support innovative technologies. The application of the latest regulatory measures, in particular the embedding of rules in smart contracts, will comply with the principles of technologically neutral regulation, which allows for a balance between innovation and stability.Prospects. Further development of PPIM requires research into the communication of DeFi with traditional finance, in particular asset tokenization and smart contracts, to minimize systemic risks. It is important to diagnose the stability of stablecoins and their impact on financial inclusion in developing countries. Regulating decentralized systems like DAOs will contribute to financial stability and define the framework for interaction with regulators. The implementation of AI requires ethical standards to ensure transparency and security. In Ukraine, the Brave1 cluster demonstrates the potential of PPPs for innovation in conditions of uncertainty, and the modernization of CSR taking into account transactional policy trends will harmonize economic and defense goals, contributing to sustainable development and adaptation of global standards to local dimensions.